2005
DOI: 10.1128/aem.71.6.3093-3099.2005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Growth Phase on Adhesion Kinetics of Escherichia coli D21g

Abstract: The influence of bacterial growth stage and the evolution of surface macromolecules on cell adhesion have been examined by using a mutant of Escherichia coli K-12. To better understand the adhesion kinetics of bacteria in the mid-exponential and stationary growth phases under flow conditions, deposition experiments were conducted in a well-controlled radial stagnation point flow (RSPF) system. Complementary cell characterization techniques were conducted in combination with the RSPF experiments to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
149
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 177 publications
(163 citation statements)
references
References 68 publications
11
149
3
Order By: Relevance
“…Hydrophobicity was measured by the microbial-adhesion-to-hydrocarbon (MATH) test, which gives a quantitative measure of the amount of cells partitioning in the hydrocarbon versus the electrolyte phase (41). The average microbial size, notably the length, width, and subsequently calculated average equivalent spherical radius, was determined from three images (n ÏŸ 20) by utilizing a phase-contrast microscope and imaging software (Matlab; MathWorks, Natick, MA) (41).…”
Section: Methodsmentioning
confidence: 99%
“…Hydrophobicity was measured by the microbial-adhesion-to-hydrocarbon (MATH) test, which gives a quantitative measure of the amount of cells partitioning in the hydrocarbon versus the electrolyte phase (41). The average microbial size, notably the length, width, and subsequently calculated average equivalent spherical radius, was determined from three images (n ÏŸ 20) by utilizing a phase-contrast microscope and imaging software (Matlab; MathWorks, Natick, MA) (41).…”
Section: Methodsmentioning
confidence: 99%
“…Among these particles some are by themselves environmental contaminants (Kessler and Hunt ;Buddemeier and Hunt 1988) while some serve as vehicles to facilitate the transport of a variety of other contaminants that otherwise would be relatively immobile without the presence of the colloids (McCarthy and Zachara 1989;Corapcioglu and Jiang 1993;Grolimund, Borkovec et al 1996;Ryan and Elimelech 1996). Different types of environmentally relevant particles have been studied, including various minerals, Rajagopalan and Chu 1982;Puls and Powell 1992;Ryde, Kihira et al 1992) bacteria and viruses, (Logan, Hilbert et al 1993;Pieper, Ryan et al 1997;Ryan, Elimelech et al 1999;Redman, Walker et al 2004;Walker, Hill et al 2005) and engineered nanoparticles (Lecoanet, Bottero et al 2004;Brant, Lecoanet et al 2005;Saleh, Phenrat et al 2005;Chen and Elimelech 2006;Espinasse, Hotze et al 2007;Jaisi, Saleh et al 2008). The transport and mobility of engineered nanoparticles have been of particular interest over the past few years due to concerns over possible environmental and health impact of these materials (Hoet, Nemmar et al 1999;Colvin 2003;Borm, Robbins et al 2006;Renn and Roco 2006;Wiesner, Lowry et al 2006).…”
Section: Overview Of Deposition Studymentioning
confidence: 99%
“…Moreover, the composition of macromolecules on the outer membrane is known to be influenced by the bacterial growth phase (Hong and Brown (2006)). In one recent study (Walker et al (2005)) it was shown that the adhesion profile of Escherichia coli was dependent on its growth phase, which was determined by the charge distribution resulting from electrostatic repulsion forces. Differences in biofouling of RO membranes have also been showed to depend on the growth stage of the bacterial species studied (Herzberg et al (2009)).…”
Section: Effect Of Bacterial Growth Stage Deposition Under Flux Condimentioning
confidence: 99%